Sourdough by science : understanding bread making for successful baking - Newman, Karyn Lynn (The Countryman Press, an imprint of W. W. Norton & Company, 2022)
"The how's and why's of perfect, easy sourdough, from a home baker and molecular scientist. Understanding how bread works makes it a far more likely to succeed, especially for home bakers. This is especially true with sourdough, considering the process: wild yeast activates a starter, the starter grows into a levain, humidity in the dough develops the crumb, and heat bakes the loaf. In Sourdough by Science, Molecular biologist Karyn Newman provides a reliable path to sourdough success by arming readers with great recipes, filled with fascinating and helpful descriptions of what's happening on a molecular level; a plan for developing skills; and an invaluable and wide-ranging troubleshooting guide. From Rustic Boule to Wild Challah, and Olive Bats to Hazelnut Buns, recipes reveal how different flours respond, when salt should be added, how to get a crisp, crackly crust. Answers to common queries and more are here, along with resources and step-by-step photos, making this an essential book for the home bread baker"--